Microscopic Simulation On The Operation And Capacity Of Toll Plaza In Malaysia - Mahdi, Mohammed Bally (2017)
Microscopic traffic simulation software has several applications, such as performance evaluation, plan improvements, traffic operation control, design, and transportation facility management. This study presents the application of the well-known traffic simulation software VISSIM in the operation of toll plazas in Malaysia. This study evaluates the overall toll operation of two types of closed system toll plazas in the Malaysian expressway to gain insight into the variables that influence toll operations, which in turn affect the actual capacity of toll plazas in terms of average and maximum queue length. VISSIM was used to build toll plaza models for the mainline and ramp toll plazas which are Juru and Jawi respectively, to study their toll operations and actual capacities. In order to simulate the toll operations at toll plazas, microscopic data were obtained for each vehicle arriving and departing the toll plazas through video recordings. Video recordings were taken from two sources. The first source was from the installed CCTV and the second source was from the PLUS CCTV cameras at the tollbooths. The collected field data of the Juru and Jawi toll plazas differed in terms of number of lanes, lane configuration, toll base fee, expressway location, traffic demand, and traffic composition characteristics. The toll plaza models were then calibrated according to the measure of effectiveness and key parameter to match real world toll operations at toll plazas. Results revealed that service time is the most important parameter for evaluating the toll operation of toll plazas. Moreover, service time for entry is much lower than the service time for exit. The findings indicated that the percentage of heavy vehicles in traffic flow has a significant impact on the queue lengths at the Juru and Jawi toll plazas. Apart from that, the models were used to predict the operation of toll plazas in the future upon implementation of full electronic toll collection (ETC). The results indicated that the implementation of full ETC at the entry of both the Juru and Jawi toll plazas did not improve the operations of the toll plazas. However, the implementation of full ETC at the exit significantly improved the toll operations. But, the implementation of full ETC at the exit of the Jawi toll plaza has negatively influenced the queue lengths of Touch 'n Go and Smart TAG lanes due to the location of the signalised intersection which is near to Jawi toll plaza. The study has managed to contribute to two major findings at the traffic operations at toll plaza. The first contribution is on the prediction of traffic operation at the toll plaza in the future after the implementation of full electronic toll collection system at conventional toll plazas. The second contribution is on the estimation of the actual capacity of the conventional toll plazas.